Breve repaso a la evolución histórica del Derecho del Trabajo - Quiñones Infante, Sergio (2016)
In this article, the author presents the theme of the historical evolution of Labour Law, analyzing the most important milestones in which it develops. Firstly, he addresses the regulation of work in the preindustrial era; then, the emergence of Labour Law as a result of historical and social factors; and finally, its evolution throughout the twentieth and twenty-first century, concluding that this development has come to be circular.